TERRORISM AND FOREIGN POLICY: NIGERIA EXPERIENCE WITH BOKO HARAM INSURANCY (2009-2015) (Abuja Journal of Sociological Studies, 2026)
Domestic environment of a country plays a significant role in her foreign policy. Since independence Nigeria has had to contend with internal security challenges. The situation got to its crescendo from 1999 when the country returned to civil rule. The escalation of Boko-haram group into a terror organization heralded backlash on Nigeria's global image. The activities of the group have wrecked serious havoc on Nigeria. Unfortunately, successive administrations have not succeeded in their fights against the group, despite the huge amount of human and financial resources committed to the war. The image of the country has also been battered. The objective of this study is to identify the implication of the Boko-Haram insurgency on foreign policy formulation in the years 2009 and 2015. It adopted Decision-Making Theory as its theoretical framework. The study adopted qualitative research method, relying on secondary source of data. The finding The study finds that the Boko-haram insurgency has little impact on Nigerian foreign policy, unlike external pressure and interest of the ruling elite. The paper  recommends strengthening of the Nigerian security architecture to prevent insurgencies and also consider both internal and external factors in foreign policy formulation and implementation.